Evaluasi Kepatuhan Petugas Pendaftaran Rawat Jalan dalam Penerapan Kebijakan Privasi Rekam Medis Elektronik di RSD K.R.M.T. Wongsonegoro - Yosefina Palimirma Andrianto; Wahyu Ratri Sukmaningsih (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
RSD K.R.M.T Wongsonegoro has implemented Electronic Medical Records (EMR) in healthcare services. However, several issues related to data security are still encountered in its implementation, including the continued use of paper-based forms, staff practices that may compromise account confidentiality, errors in patient data entry, and system disruptions affecting data availability. This study aimed to evaluate the compliance of Outpatient Registration Officers with the Electronic Medical Record privacy policy based on three main aspects of information security: privacy, integrity, and availability. This study employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews with Outpatient Registration Officers and direct field observations. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using triangulation of interview and observation results. The results showed that, in terms of privacy, officers understood the importance of maintaining data confidentiality and used personal accounts; however, practices such as recording usernames were still found, which may pose security risks. Regarding integrity, officers generally followed data entry procedures and performed data verification, although accuracy was not always consistent during periods of high workload. In terms of availability, the EMR system supported healthcare services, but system disruptions still occurred and hindered access to patient data. It can be concluded that staff compliance with EMR data security policies was generally good but not yet optimal. Therefore, improvements in supervision, staff compliance, and system reliability are needed to enhance data security and service quality.